Penerapan Teknik Distraksi Visual (Membaca) Terhadap Penurunan Halusinasi pada Pasien Skizofrenia - Kusuma, Pradana May Yudha Chandra; Amin, Muhammad Khoirul; Pinilih, Sambodo Sriadi; Astuti, Retna Tri (Borobudur Nursing Review, 2025)
characterized by disorganization of personality functioning. One of the symptoms of schizophrenia is hallucinations. The prevalence of hallucinations in Indonesia is quite high, with data from Dr. Soerojo Magelang Mental Hospital showing the number of hallucination patients reaching 1,425 (2020), 1,500 (2021), and 1,250 (2022). Interventions to overcome hallucinations can be non-pharmacological interventions and one of them is visual distraction by reading. This case study aims to identify the application of visual distraction techniques (reading) in schizophrenia patients with hallucinatory sensory perception disorders. The research subjects were two male patients (Patient 1, 36 years old; Patient 2, 53 years old) with a diagnosis of schizophrenia and auditory/visual hallucinations, who were in the condemning phase. The intervention was conducted for 6 meetings in 2 weeks. Results showed a decrease in AHRS scores in Patient 1 from 29 (severe) to 12 (moderate), and Patient 2 from 20 (moderate) to 5 (mild). This decrease indicates the effectiveness of the reading distraction technique in relieving hallucination symptoms and improving the patient's ability to control themselves. This study recommends the application of reading distraction techniques as part of non-pharmacological interventions in mental nursing care. This scientific work recommends that the hospital can continue the action of journaling therapy on an ongoing basis.